∫ − ∞ ∞ ( x 2 + 1 ) 3 d x
If the integral above equals to b a π for coprime positive integers a , b , find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
did the same way
Well, I will use Contour integration here.
Let's just assume a contour C in the argand plane as a semicircle with radius a with positive complex axis in the circle, then the following will be our integral
∫ − a a ( z 2 + 1 ) 3 d z
By Cauchy's theorem(as in the contour they all will homotopic)-
∫ C ( z 2 + 1 ) 3 d z = ∫ − a a ( z 2 + 1 ) 3 d z + ∫ a r c ( z 2 + 1 ) 3 d z
∫ − a a ( z 2 + 1 ) 3 d z = ∫ C ( z 2 + 1 ) 3 d z − ∫ a r c ( z 2 + 1 ) 3 d z
First, let's compute our line integral first
By Cauchy's General Formula
f ( n ) ( z 0 ) = 2 π ι n ! ∫ C ( z − z 0 ) n + 1 f ( z )
Now, let's try to make our integral in this form
We can write it as
∫ C ( z − i ) 3 ( z + i ) 3 1 , Then f ( z ) = ( z + i ) 3 1 , z 0 = i
Why we write like this? There is one more possibility, why we didn't chose that? Because the function f ( z ) is not analytic in the contour we have chosen then.
As a result of substituting,
∫ C ( z 2 + 1 ) 3 d z = 8 3 π
Just substitute in the Cauchy's Formula, differentiate twice then put z = i , you are done!
Hence,
∫ − a a ( z 2 + 1 ) 3 d z = 8 3 π − ∫ a r c ( z 2 + 1 ) 3 d z
For our 2nd integral, use Estimation Lemma or ML inequality,
∣ ∣ ∣ ∣ ∣ ∫ a r c ( z 2 + 1 ) 3 d z ∣ ∣ ∣ ∣ ∣ ≤ ( a 2 − 1 ) 3 a π
As a ⇒ ∞ , ( a 2 − 1 ) 3 a π ⇒ 0
Therefore, ∫ a r c ( z 2 + 1 ) 3 d z ⇒ 0
As a result, we are done with our answer,
∫ − ∞ ∞ ( x 2 + 1 ) 3 d x =
8 3 π
This is my first solution involving complex analysis so if anyone finds any flaw, please let me know.
Log in to reply
Simply putting x=tan(\theta), yields the answer in seconds, there's no need for such a long solution.
Log in to reply
Totally agree with you! Just that I was practicing and yeah Level 5 rating(when I solved) got me thinking of this straightaway.
Problem Loading...
Note Loading...
Set Loading...
We shall make a simple substitution here.
Let x = tan ( θ )
Hence:
d x = sec 2 ( θ ) d θ ⇒ 1 + x 2 d x = d θ
The limits correspondingly change to 2 − π & 2 π
I = ∫ − 2 π 2 π ( sec 2 θ ) 2 d θ = ∫ − 2 π 2 π d θ cos 4 θ
I = ∫ − 2 π 2 π d θ cos 4 θ = 8 3 π
Note
If you want to evaluate I = ∫ − 2 π 2 π d θ cos 4 θ take cos 4 θ = ( 2 1 + cos 2 θ ) 2